The Ancient Relationship between Grazing Animals and Grasslands - Wade Parsons (Symphony in the Flint Hills, 2010)
It has often been said tallgrass prairies are the result of fire and climate. That statement is true, but it is only part of the story. The development of plant communities on Kansas pasturelands involves a complex progression of factors still being investigated by scientists. Some of those processes began so long ago we seldom consider their importance in the establishment of North America’s prairies.
Keywords: bison; grazing; grassland; prairie; grass; ancient; roots; tallgrass; fire; plant; pastureland; prehistoric; Oligocene; Pleistocene Ice Age; mammals; migration; continents; Miocene; silica; fodder; food; Pliocene; global; fossils; mammoth; rhino; caribou; American lion; musk oxen; dire wolves; saber-toothed cats; herbivores; carnivores; DNA; Latifrons; antiquus; Paleo-Indians; Konza; biological; conservation; ecosystem; Tallgrass Prairie National Preserve; Chase County; Wind Cave